2011
DOI: 10.1177/1531003511400627
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Resuscitation in the Setting of Vascular Injury

Abstract: Damage control surgery with the principles of expeditious control of hemorrhage and contamination, followed by predominant crystalloid resuscitation in the intensive care unit has saved the lives of many severely injured trauma patients. Unfortunately, crystalloid resuscitation has too often led to worsening of coagulopathy in the setting of vascular injury. The recent conflicts in Iraq and Afghanistan have created injured patients with severe vascular injury and massive soft tissue destruction creating early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Hence increased heme degradation may be the result of increased hemolysis, and may explain why heme biosynthesis was not increased in our study. Studies from Fox et al indicate that high erythrocyte creatine levels are an indicator of hemolysis [ 39 ]. In addition, Hebbe et al concluded that red blood cell survival is the gold-standard test for hemolysis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence increased heme degradation may be the result of increased hemolysis, and may explain why heme biosynthesis was not increased in our study. Studies from Fox et al indicate that high erythrocyte creatine levels are an indicator of hemolysis [ 39 ]. In addition, Hebbe et al concluded that red blood cell survival is the gold-standard test for hemolysis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Fox et al indicate that high erythrocyte creatine levels are an indicator of hemolysis [ 39 ]. In addition, Hebbe et al concluded that red blood cell survival is the gold-standard test for hemolysis [ 39 ]. They found that patients with PAH had subclinical hemolysis, as shown by higher EC levels [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In polytrauma patients it has been associated with increased bleeding morbidity, higher transfusion requirements, increased risk of organ dysfunction, longer critical care stays and increased overall mortality [ 12 14 ]. The severity of post traumatic coagulopathy has been shown to directly correlate with overall injury severity [ 15 ]. Once established this state is extremely difficult to correct and is a potent cause of early death in such patients.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In civilian settings, the recent multi-institutional investigation by DuBose and colleagues reported 7.8 % vascular injuries to the intra-abdominal vessels admitted to 13 US trauma facilities [5••]. The increasing incidence of vascular injuries arriving to medical care in the USA can be associated with truncated on-scene times, evolving prehospital management, and hemostatic resuscitation [6].…”
Section: Introductionmentioning
confidence: 99%